Research on treatment-related aspects of depression from India in the preceding decade (2014–2023): An updated systematic review - Alankrit Jaiswal; S Umesh; Nishant Goyal (Indian Journal of Psychiatry)
Background: The National Mental Health Survey reports a prevalence of 2.7% for depressive disorders in India. The services for depression patients may be organized differently in India as compared to Western countries. It is important to consider studies conducted in India to determine effective interventions for depression catered specifically to the needs of the Indian population. We intended to systematically review the articles studying the usefulness of various treatment modalities in the management of depression in the Indian context. Materials and Methods: We searched PubMed, Google Scholar, and ScienceDirect to identify studies published in peer-reviewed English language journals. All articles from India evaluating the clinical efficacy of anti-depressants, electro-convulsive therapy, repetitive transcranial magnetic stimulation, and psychological interventions for the management of depression were evaluated. Data were extracted using standard procedures. Results: A total of 36 studies were included in the review. Out of those, 15 were studies on drug efficacy, five on neuro-modulation, nine on psycho-social interventions, four on adverse effects, and three on miscellaneous studies. Innovations were seen in the field of neuro-modulation and psycho-social intervention. Trials on drug efficacy and adverse drug reactions require larger sample sizes, more studies on newer agents, and more robust study designs. Conclusion: More research is needed to understand the effectiveness and potential negative effects of depression treatments in India. Studies on ketamine have been inconclusive, and existing research on pharmacological agents is limited. Neuro-modulation studies show promise, but larger-scale studies are needed. Innovative psychological interventions tailored to the Indian population include community-based and digital technology-driven care.